Cyclic mechanical stretch up-regulates hepatoma-derived growth factor expression in cultured rat aortic smooth muscle cells. Issue 2 (16th March 2018) - Kao, Ying-Hsien; Chen, Po-Han; Sun, Cheuk-Kwan; Chang, Yo-Chen; Lin, Yu-Chun; Tsai, Ming-Shian; Lee, Po-Huang; Cheng, Cheng-I
Abstract : Hepatoma-derived growth factor (HDGF) is a potent mitogen for vascular smooth muscle cells (SMCs) during embryogenesis and injury repair of vessel walls. Whether mechanical stimuli modulate HDGF expression remains unknown. The present study aimed at investigating whether cyclic mechanical stretch plays a regulatory role in HDGF expression and regenerative cytokine production in aortic SMCs. A SMC cell line was grown on a silicone-based elastomer chamber with extracellular matrix coatings (either type I collagen or fibronectin) and received cyclic and uniaxial mechanical stretches with 10% deformation at frequency 1 Hz. Morphological observation showed that fibronectin coating provided better cell adhesion and spreading and that consecutive 6 h of cyclic mechanical stretch remarkably induced reorientation and realignment of SMCs. Western blotting detection demonstrated that continuous mechanical stimuli elicited up-regulation of HDGF and proliferative cell nuclear antigen, a cell proliferative marker. Signal kinetic profiling study indicated that cyclic mechanical stretch induced signaling activity in RhoA/ROCK and PI3K/Akt cascades. Kinase inhibition study further showed that blockade of PI3K activity suppressed the stretch-induced tumor necrosis factor-α (TNF-α), whereas RhoA/ROCK inhibition significantly blunted the interleukin-6 (IL-6) production and HDGF overexpression. Moreover, siRNA-mediated HDGF gene silencing significantly suppressed constitutive expression of IL-6, but not TNF-α, in SMCs. These findings support the role of HDGF in maintaining vascular expression of IL-6, which has been regarded a crucial regenerative factor for acute vascular injury. In conclusion, cyclic mechanical stretch may maintain constitutive expression of HDGF in vascular walls and be regarded an important biophysical regulator in vascular regeneration.